2021
DOI: 10.7759/cureus.14399
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Congenital Coronary Artery Anomalies in Patients Undergoing Coronary Angiography at a Tertiary Care Hospital of Northern India

Abstract: Objectives: To evaluate the prevalence and pattern of congenital coronary artery anomalies (CAAs) in the adult population undergoing catheter coronary angiography.Methods: The coronary angiograms done between October 2015 and September 2020 were reviewed for the presence of coronary anomalies based upon Angelini's classification. The medical record of patients with anomalies was reviewed for symptomatology and indication of angiography.Results: CAAs were found in 129 (87 males and 42 females) of 6,258 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
7
11
1
Order By: Relevance
“…Similarly, high prevalence rates have been reported by (0.22%). 11 However, some studies have shown lower occurrence rates, with a prevalence of 0.10% and 0.1%. 12,13 With inter-arterial RCA patients showed the increased risk for myocardial ischemia, which can lead to life-threatening clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high prevalence rates have been reported by (0.22%). 11 However, some studies have shown lower occurrence rates, with a prevalence of 0.10% and 0.1%. 12,13 With inter-arterial RCA patients showed the increased risk for myocardial ischemia, which can lead to life-threatening clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of this CAA variant are negligible. 11,13 Thirteen patients (0.36 %) had RCAs that originated in the posterior wall of the right coronary sinus. It has a relatively low incidence rate of 0.16 percent and may be harmless.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst which 0.51% incidence was shown in the anomalous area right coronary artery (RCA) from a left coronary sinus (LCS), thus making it the leading type of anomaly. Similarly, Jeet R et al reported an incidence of 2.06% of coronary artery anomaly after reviewing, 6,258 coronary angiograms in the age ranging from 51-60 years [1]. With 1.29 percent, the most prevalent abnormality was anomalous origin and course of arteries, followed by intrinsic abnormalities of coronary arterial system anomalies of coronary termination and anomalous anastomotic vessels, at 0.7 percent and 0.03 percent, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…The rare congenital disorder "Coronary Artery Anomalies (CAA)" varies differently in clinical presentation and on average 1% of the adult population represents in autopsy [1]. Out of 80% of the coronary artery anomalies are benign in nature and on angiographic profile, 0.1%-1.3% of patients are reported of anomalous coronary arteries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to the risk of adverse cardiac events CCAA can be separated into three kinds: benign coronary anomalies (BCA), potentially serious coronary anomalies(PSCA), serious coronary anomalies(SCA); which refers to CCAA-BCA, CCAA-PSCA and CCAA-SCA, in order to help clinicians better understand and identify the related diseases. See Table 1 for abbreviations and Table 2 for details (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%